A Comment on "Patience, Risk-Taking, and Human Capital Investment Across Countries" by Hanushek et al. (2021) - Alexandra de Gendre; Jan Feld; Nicolás Salamanca (Institute for Replication (I4R), 2023)
Hanushek et al. (2021) test how country-level measures of patience and risk-taking from the Global Preference Survey predict student performance on the Programme for International Student Assessment (PISA) math test. They find that country-level patience positively predicts math test scores and country-level risk-taking negatively predicts math test scores. They find similar results when holding country of residence characteristics constant and focusing on the preferences of the country of origin of migrants. We have checked the computational reproducibility and find that the data and analysis script provided by the authors allowed us to exactly reproduce the main tables in the paper. We also checked the robustness replicability by testing how robust the results are to decisions about imputation, weighting, operationalization of dependent variables, choice of control variables, and the inclusion of highly leveraged observations. We see that results are generally robust, though statistical significance of the risk-taking coefficient in the migrant analysis hinges on whether a control for OECD country of residence is included. Finally, we check the conceptual replicability of the results by using data from the Trends in International Mathematics and Science Study (TIMSS) instead of PISA - a different dataset with a different standardized test. This exercise shows that their results are robust to expanding the analysis to countries participating in both PISA and TIMSS.
Keywords: 330